The International Society for Engineering Pedagogy (IGIP) and the New Pedagogic Challenges in Engineering Education - Michael A. Auer (Высшее образование в России)
The article outlines the new tendencies and prospects in engineering education and engineering pedagogy. The new trends and questions result in a need to evolve new educational practices, especially in engineering pedagogy in order to provide the most effective learning experiences for engineering students of the 21st century. A new look at the didactic and pedagogic concepts that presently form the basis of engineering education is required. IGIP has proposed a Prototype Curriculum for engineering pedagogy and has developed the accreditation criteria for engineering pedagogy programs